139=-5-2(4+8P)

Simple and best practice solution for 139=-5-2(4+8P) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 139=-5-2(4+8P) equation:


Simplifying
139 = -5 + -2(4 + 8P)
139 = -5 + (4 * -2 + 8P * -2)
139 = -5 + (-8 + -16P)

Combine like terms: -5 + -8 = -13
139 = -13 + -16P

Solving
139 = -13 + -16P

Solving for variable 'P'.

Move all terms containing P to the left, all other terms to the right.

Add '16P' to each side of the equation.
139 + 16P = -13 + -16P + 16P

Combine like terms: -16P + 16P = 0
139 + 16P = -13 + 0
139 + 16P = -13

Add '-139' to each side of the equation.
139 + -139 + 16P = -13 + -139

Combine like terms: 139 + -139 = 0
0 + 16P = -13 + -139
16P = -13 + -139

Combine like terms: -13 + -139 = -152
16P = -152

Divide each side by '16'.
P = -9.5

Simplifying
P = -9.5

See similar equations:

| (5x^3y^2-3xy^5+12x^2)-(-9x^2-8x^3y^2+2xy^5)=0 | | 4x-9=-6+-5x | | 3x(-3)+b= | | 7-3a=11+a | | X(15x+11x)+2=0 | | 4.9t^2-24.5t+2=0 | | c^2-3c-18= | | 6+3(13-2)-25= | | 5x+2-4x=5+8 | | -5y+7y=10 | | 2(4p+3)-3(3p-6)-16p= | | -6(7x-1)=-8x+9(-3x+4) | | .5(4m+5)=-6 | | t^2-24.5t+2=0 | | 2a/3a-3/4=3a/4a | | h(t)=-16t^2+20t+4 | | 7+3a=11-a | | 3(4x-6)=2(4x-3)-(x+8) | | 13.04=f+8.25 | | 9n-3n= | | 13(t+1)-3(2+4t)=48 | | 180=(9x+4)-y | | -15=-5t^2+30t | | 9-3x+5x=-11 | | 2-(x+3)=6 | | 5x+4=37 | | X^2+6x-34=0 | | y+x=y-x | | 2(x-5)+2x=x+3x-2x | | 180+(9x+4)=y | | 20-0.75x+0.55x=10 | | 55+8(25)=x |

Equations solver categories